Macroeconomic policy and stock market dynamics in Iraqi commercial banks: Evidence from a PLS-SEM approach (2010–2025) - Qasim Hameed Naser (Nur Science Institute, 2026)
The connection between macroeconomic policy and stock market dynamics of Iraqi private commercial banks is a gap in the literature which has traditionally neglected banking sectors in rentier economies. The oil-dependent economy in Iraq is a great place to look into how macroeconomic conditions influence financial markets. We take annual data for banks listed on the Iraq Stock Exchange for 2010-2025 and use the stock performance indicators to measure the influence of the macroeconomy as the dependent variable. Macroeconomic policy is modeled as a composite latent variable including M2 (money supply), inflation, and oil prices. The study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS and SPSS to test direct and indirect relationships. Higher liquidity and oil prices enhance banking stock performance, while inflation weakens these effects. It can be concluded that macroeconomic policy has an impact on stock markets mainly in terms of liquidity and confidence in the market by investors. The authors also highlight that macroeconomic indicators can be used as a tool of information for investors and policymakers in rentier economies.